2004
DOI: 10.1104/pp.103.038083
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Genome Evolution Revealed by Comparative Sequence Analysis of Orthologous Regions from Four Triticeae Genomes

Abstract: Bread wheat (Triticum aestivum) is an allohexaploid species, consisting of three subgenomes (A, B, and D). To study the molecular evolution of these closely related genomes, we compared the sequence of a 307-kb physical contig covering the high molecular weight (HMW)-glutenin locus from the A genome of durum wheat (Triticum turgidum, AABB) with the orthologous regions from the B genome of the same wheat and the D genome of the diploid wheat Aegilops tauschii Kong et al., 2004). Although gene colinearity appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 52 publications
10
90
0
Order By: Relevance
“…Comparison of the conserved features identified several molecular mechanisms underlying these rearrangements. In addition to insertions and deletions of LTR retrotransposons, which have also been described in previous studies in wheat (Wicker et al 2003a;Gu et al 2004), the pattern of conservation of the Romani retrotransposons provides interesting insight into the evolution of this interval ( Fig. 2A).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Comparison of the conserved features identified several molecular mechanisms underlying these rearrangements. In addition to insertions and deletions of LTR retrotransposons, which have also been described in previous studies in wheat (Wicker et al 2003a;Gu et al 2004), the pattern of conservation of the Romani retrotransposons provides interesting insight into the evolution of this interval ( Fig. 2A).…”
Section: Resultssupporting
confidence: 61%
“…Species from the grass family provide an excellent model for such studies, as extensive genetic colinearity among several grass species has been described despite very heterogenous genome sizes and evolutionary divergence times of over 60 million years (for review, see Devos and Gale 2000;Keller and Feuillet 2000). Recent large-scale comparative studies in maize, sorghum, rice, barley, and wheat have revealed a mosaic organization of conserved and nonconserved genes at orthologous loci and many small rearrangements (Dubcovsky et al 2001;Ramakrishna et al 2002;Song et al 2002;Brunner et al 2003;Gu et al 2003Gu et al , 2004Ilic et al 2003;Guyot et al 2004). Interestingly, intraspecific comparative studies in maize have also shown disruption of colinearity, not only in the intergenic regions, but also in the gene space (Fu and Dooner 2002;Song and Messing 2003).…”
mentioning
confidence: 99%
“…Kashkush et al (2002) analyzed F 1 intergeneric Triticeae hybrids for alterations of gene structure and expression: results indicate genetic and epigenetic changes occurred at the F 1 stage, causing gene loss, silencing and activation. Gu et al (2004) elucidated possible mechanisms of gene silencing in wheat and concluded retrotransposon insertions were a primary cause. After gene duplication events, wheat has retained the functionality of some genes and silenced others.…”
Section: Agp-lmentioning
confidence: 99%
“…Each genome is homoeologous to the other genomes and consists of very similar orthologous loci. Gu et al (2004) suggest the A and D genomes were derived from a common ancestor after separation of the B genome species. Subsequently, the A and B genomes were united when an A genome donor, T. urartu, crossed with an unknown B genome donor and produced T. turgidum.…”
Section: Introductionmentioning
confidence: 99%
“…Support for this hypothesis comes from the analysis of gene expression in polyploids, where genes show asynchronous expression on a temporal and spatial level depending on the parental genome of origin (Adams et al 2003;Gu et al 2004), the appearance of apomictic traits in hybrids of related sexual plants, allo-polyploids or paleo-polyploids (for example, Antennaria, Sorghum and Arabidopsis; see Carman 2001see Carman , 2007, and the close morphological and molecular relationships observed during sexual and apomictic processes. Recent support also comes from a study of apomixis in Boechera where transcriptomic profiling was used to compare allele-specific gene expression in ovules from related sexual and apomictic plants (Sharbel et al 2009).…”
Section: Interspecific Hybridisation May Lead To the Initiation Of Apmentioning
confidence: 99%